2016
DOI: 10.18632/oncotarget.9551
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation to the sigma-2 ligand SV119 overcomes uptake blockade and converts dm-Erastin into a potent pancreatic cancer therapeutic

Abstract: Cancer-selective drug delivery is an important concept in improving treatment while minimizing off-site toxicities, and sigma-2 receptors, which are overexpressed in solid tumors, represent attractive pharmacologic targets. Select sigma-2 ligands have been shown to be rapidly internalized selectively into cancer cells while retaining the capacity to deliver small molecules as drug cargoes. We utilized the sigma-2-based drug delivery concept to convert Erastin, a clinically underperforming drug, into a potent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Our results reiterate the importance of targeting SLC7A11 in both CAFs and PDAC cells.Consistent with this, conditional knockout of SLC7A11 in only the tumour compartment of KPC tumours did not affect mouse survival, but interestingly it did decrease intra-tumoural fibrosis, implying pro-fibrogenic cross-talk between tumour and stromal cells had been disrupted.Notably, these results were reproduced in vitro, whereby SLC7A11 knockdown in isolated CAFs from the KPC mouse tumours significantly reduced their proliferation but had no effect in KPC PDAC cells. Our results are in striking contrast to prior KPC mouse PDAC models in which SLC7A11 was inhibited via a modified form of erastin(20), systemic deletion of SLC7A11 or cysteinase enzyme treatment(21) and significantly reduced tumour growth. What is important to note is that these studies did not selectively target PDAC tumour cells and these mouse models are characterised as having a prominent fibrotic tumour stroma.…”
contrasting
confidence: 97%
See 2 more Smart Citations
“…Our results reiterate the importance of targeting SLC7A11 in both CAFs and PDAC cells.Consistent with this, conditional knockout of SLC7A11 in only the tumour compartment of KPC tumours did not affect mouse survival, but interestingly it did decrease intra-tumoural fibrosis, implying pro-fibrogenic cross-talk between tumour and stromal cells had been disrupted.Notably, these results were reproduced in vitro, whereby SLC7A11 knockdown in isolated CAFs from the KPC mouse tumours significantly reduced their proliferation but had no effect in KPC PDAC cells. Our results are in striking contrast to prior KPC mouse PDAC models in which SLC7A11 was inhibited via a modified form of erastin(20), systemic deletion of SLC7A11 or cysteinase enzyme treatment(21) and significantly reduced tumour growth. What is important to note is that these studies did not selectively target PDAC tumour cells and these mouse models are characterised as having a prominent fibrotic tumour stroma.…”
contrasting
confidence: 97%
“…What is important to note is that these studies did not selectively target PDAC tumour cells and these mouse models are characterised as having a prominent fibrotic tumour stroma. Therefore, it is likely that SLC7A11 inhibition would have also affected CAFs pro-tumour/fibrotic activity which would have contributed to the reduced tumour growth.Both prior studies also demonstrated that SLC7A11 inhibition(20) or systemic genetic deletion(21) in the KPC mouse model increased median survival, highlighting the efficacy of SLC7A11 inhibition as a standalone therapeutic approach. To complement this work, we opted for an orthotopic model of PDAC with a defined pre-mortality endpoint.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In this cell line, where σ 2 ligands previously displayed promising in vitro and in vivo efficacy [37], we assessed the expression level of P-gp as a mean to determine what role, if any, this efflux pump plays in the context of the cytotoxicity of our drugs. Western blot analysis clearly showed no expression of the efflux pump in KP02 cells, so that activity at the P-gp of these compounds did not seem to be involved in their action in this cell line (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The sigma-2 receptor is a potential target for cancer therapeutics 6,23 . Sigma-2 ligands have been shown to induce cytotoxicity in cancer cells as a single agent, a drug delivery agent 24,25 and a sensitizer to other anticancer drugs in cell culture and in animal models. Sigma-2 ligands trigger cell death by inducing lysosome dysfunction, ROS production, caspase-independent, and caspase-dependent events 2631 .…”
Section: Introductionmentioning
confidence: 99%